Microclimatic variations of land surface temperature on Galindez Island (western part of the Antarctic Peninsula) - Savenets, M.; Pysarenko, L.; Pishniak, D. (Ukrainian Antarctic Journal, 2020)
The study presents analysis of microclimatic conditions on Galindez Island (western part of the Antarctic Peninsula), in particular: seasonal variability and spatial heterogeneity. Based on land surface temperature (LST) data derived from loggers and MicroClimate Monitoring Station, we analyzed areas with active growth of local plants. Seasonal variations formed mainly under annual and semi-annual cycles, with no dependencies of amplitudes and phases form area location. LST highly correlates with air temperature and total incoming irradiance. It is emphasized that spatial orientation of relief microforms plays the most significant role for LST formation on micro-level. Using cluster analysis, it was found that temperature loggers which are located along shoreline and oriented to the north–north-east could be grouped by similar LST distribution.